A study of the chemical effect of marble and granite slurry on green mortar compressive strength - Amin, Shereen K. (2021)
The study revealed that by replacing 5% of cement in (NC5) mix, 10% of sand in (NF10) mix, as well as 5% of cement and 10% of sand in (NC5 + NF10) mix, by granite waste powder, the compressive strength values increased by 33%, 39%, and 41%, respectively. This was due to the presence of more than 26% fine free silica particles in granite which undergo pozzolanic reaction with calcium hydroxide present in mortar pores producing calcium silicate hydrate (CSH) crystals resulting in high strength to the cement mortar. For the same mixes containing marble powder, the compressive strength showed less values by − 14%, 10%, and 0% for NC5, NF10, and NC5 + NF10 mixes, respectively, when compared to the control mix values.